Electronic Structure of the YH3 Phase from Angle-Resolved Photoemission Spectroscopy - Hayoz, J.; Koitzsch, Christian; Bovet, M.; Naumovic, D.; Schlapbach, Louis; Aebi, Philipp (My University, 2003)
Yttrium can be loaded with hydrogen up to high concentrations causing dramatic structural and electronic changes of the host lattice. We report on angle-resolved photoemission experiments of the Y trihydride phase. Most importantly, we find the absence of metal d bands at the Fermi level and a set of flat, H-induced bands located at much higher binding energy than predicted, indicating an increased electron affinity at H sites.